Understanding the role of Toll-like receptors in lung cancer immunity and immunotherapy - Hoden, Bettina; DeRubeis, David; Martinez-Moczygemba, Margarita; Ramos, Kenneth S.; Zhang, Dekai (Frontiers in Immunology, 2022)
Lung cancer is currently the leading cause of cancer-related deaths worldwide. Significant improvements in lung cancer therapeutics have relied on a better understanding of lung cancer immunity and the development of novel immunotherapies, as best exemplified by the introduction of PD-1/PD-L1-based therapies. However, this improvement is limited to lung cancer patients who respond to anti-PD-1 immunotherapy. Further improvements in immunotherapy may benefit from a better understanding of innate immune response mechanisms in the lung. Toll-like receptors (TLRs) are a key component of the innate immune response and mediate the early recognition of pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). TLR signaling modulates the tumor microenvironment from “cold” to “hot” leading to immune sensitization of tumor cells and improved patient prognosis. In addition, TLR signaling activates the adaptive immune response to improve the response to cancer immunotherapy through the regulation of anti-tumor T cell activity. This review will highlight recent progress in our understanding of the role of TLRs in lung cancer immunity and immunotherapy.